Human Normal Bronchial Epithelial Cells: A Novel In Vitro Cell Model for Toxicity Evaluation - Feng, Wenqiang; Guo, Juanjuan; Huang, Haiyan; Xia, Bo; Liu, Hongya; Li, Jie; Lin, Shaolin; Li, Tiyuan; Liu, Jianjun; Li, Hui (PLOS ONE, 2015)
Human normal cell-based systems are needed for drug discovery and toxicity evaluation. hTERT or viral genes transduced human cells are currently widely used for these studies, while these cells exhibited abnormal differentiation potential or response to biological and chemical signals. In this study, we established human normal bronchial epithelial cells (HNBEC) using a defined primary epithelial cell culture medium without transduction of exogenous genes. This system may involve decreased IL-1 signaling and enhanced Wnt signaling in cells. Our data demonstrated that HNBEC exhibited a normal diploid karyotype. They formed well-defined spheres in matrigel 3D culture while cancer cells (HeLa) formed disorganized aggregates. HNBEC cells possessed a normal cellular response to DNA damage and did not induce tumor formation in vivo by xenograft assays. Importantly, we assessed the potential of these cells in toxicity evaluation of the common occupational toxicants that may affect human respiratory system. Our results demonstrated that HNBEC cells are more sensitive to exposure of 10 20 nm-sized SiO2, Cr(VI) and B(a)P compared to 16HBE cells (a SV40-immortalized human bronchial epithelial cells). This study provides a novel in vitro human cells-based model for toxicity evaluation, may also be facilitating studies in basic cell biology, cancer biology and drug discovery.